Negative electrode material and preparation method and application thereof
By wrapping and distributing one-dimensional fast ion conductors on the surface of the active material of the negative electrode material, the problem of high tortuosity of lithium ions transmission in the negative electrode sheet is solved, and the rapid transmission of lithium ions and the improvement of battery performance is achieved.
Patent Information
- Application Number
- CN202411728351.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, the lithium ion transmission degree of the negative electrode sheet is relatively tumultuous, which makes it difficult for lithium ions to diffuse into the negative electrode during large-scale charging, which easily leads to short circuits in lithium excretion and internal, reducing the battery life and bringing safety hazards.
A negative electrode material is used, and one-dimensional fast ion conductor is distributed on the surface of its active material. By limiting the transmission direction of lithium ions, the tortuosity of lithium ions transmission is reduced, so that lithium ions can be quickly transmitted along the one-dimensional fast ion conductor to the inside of the negative electrode.
It effectively reduces the tortuosity of lithium ions to prevent the aggregation and precipitation of lithium ions on the negative electrode surface, improves the charging rate and rate performance of the battery, reduces the risk of battery short circuit, and improves the cycling performance.
Smart Images

Figure CN119560564A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a negative electrode material and a preparation method and application thereof. Background Art
[0002] The tortuosity of lithium ion transmission in the negative electrode has an important impact on its performance. When the transmission tortuosity is relatively high, the internal resistance of ion transmission is relatively large. When charging at a high rate, the lithium ions transmitted to the negative electrode side will not have time to diffuse into the interior of the negative electrode, and will aggregate and precipitate on the surface of the negative electrode. When lithium precipitation is severe, the battery will have an internal short circuit, which not only reduces the service life of the battery, but also brings serious safety hazards. Reducing the tortuosity of lithium ion transmission is an important strategy to improve the high-rate charging performance of the battery.
[0003] Therefore, how to reduce the tortuosity of lithium ion transmission in the negative electrode is a difficult problem that needs to be solved urgently. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention aims to provide a negative electrode material and its preparation method and application. In the negative electrode material provided by the present invention, a one-dimensional fast ion conductor is wound and distributed on the surface of the active material, which can effectively reduce the tortuosity of lithium ion transmission of the negative electrode plate.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a negative electrode material, comprising an active substance, and a one-dimensional fast ion conductor entangled and distributed on the surface of the active substance; the one-dimensional fast ion conductor has an aspect ratio of 50-200, for example, it can be 50, 55, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 195 or 200, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0007] In the negative electrode material provided by the present invention, a one-dimensional fast ion conductor is entangled and distributed on the surface of the active material. Due to the limitation of the one-dimensional structure of the fast ion conductor, lithium ions can only be transmitted along a one-dimensional direction. Therefore, when the negative electrode material is used to prepare the negative electrode pole piece, the tortuosity of lithium ion transmission can be effectively reduced, so that the lithium ions on the surface of the negative electrode pole piece can be quickly transmitted to the interior of the entire negative electrode along the one-dimensional fast ion conductor, thereby effectively preventing the lithium ions from aggregating and precipitating on the surface of the negative electrode, thereby increasing the charging rate of the battery, improving the rate performance, and reducing the risk of battery short circuit.
[0008] The one-dimensional fast ion conductor of the present invention has a high aspect ratio, and the one-dimensional fast ion conductors are entangled with each other, which can effectively improve the cohesion of the pole piece, thereby avoiding the influence of volume change or thermal stress on the pole piece, which helps to improve the cycle performance of the battery. At the same time, the one-dimensional fast ion conductor with a limited aspect ratio range can be used to allow the one-dimensional fast ion conductor to be evenly wound on the surface of the active material to avoid agglomeration, thereby reducing the tortuosity of lithium ion transmission and enabling the battery to achieve fast charging and discharging.
[0009] The one-dimensional fast ion conductor of the present invention has a stable structure and can repeatedly insert and remove lithium without being pulverized and broken. In addition, the one-dimensional fast ion conductor is relatively soft in texture and will not be brittlely fractured during the battery assembly process, and the structure can be kept intact.
[0010] Preferably, the active material comprises graphite and / or silicon-carbon material.
[0011] Preferably, the graphite includes primary graphite particles and / or secondary graphite particles.
[0012] Preferably, the particle size range of the active substance is 1-50 μm, wherein the particle size of a single active substance can be, for example, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 40 μm or 50 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] Preferably, the lithium ion conductivity of the one-dimensional fast ion conductor is ≥10 -5 S / cm, for example, can be 1×10 -5 S / cm, 1.1×10 -5 S / cm, 1.2×10 -5 S / cm, 1.3×10 -5 S / cm, 1.5×10 -5 S / cm, 2×10 -5 S / cm, 3×10 -5 S / cm, 5×10 -5 S / cm, 1×10 -4 S / cm, 5×10 -4 S / cm, 1×10 -3 S / cm, 5×10 -3 S / cm or 1×10 -2 S / cm, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0014] In the present invention, the one-dimensional fast ion conductor has a higher lithium ion transmission rate after lithium is inserted, and the lithium ion conductivity meets the above range.
[0015] Preferably, the electronic conductivity of the one-dimensional fast ion conductor is greater than 10 -6 S / cm, for example, can be 10 -5 S / cm, 10 - 4 S / cm, 10 -3 S / cm, 10 -2 S / cm, 10 -1 S / cm, 1S / cm, 10S / cm, 10 2 S / cm, 10 3 S / cm, 10 4 S / cm, 10 5 S / cm, 10 6 S / cm, 10 7 S / cm or 10 8 S / cm, etc., but not limited to the listed values, other values not listed in the numerical range are also applicable, preferably ≥10 -1 S / cm.
[0016] In the present invention, the one-dimensional fast ion conductor can be electron-conducting or electron-nonconducting, and both can achieve the goal of reducing the tortuosity of lithium ion transmission. -6 S / cm can produce an additional effect: it can reduce the use of conductive agents in the negative electrode, thereby reducing the electron transport tortuosity of the negative electrode and increasing the battery energy density. Furthermore, when the one-dimensional fast ion conductor has a high electronic conductivity (≥10 -1 S / cm), the effect is better, and the conductive agent in the negative electrode plate can be further reduced or even eliminated, so that the negative electrode plate has a lower electron transfer tortuosity, which can effectively improve the energy density of the battery. At the same time, the electronic conductivity of the negative electrode plate is higher and the ohmic polarization is smaller.
[0017] In the present invention, when the lithium ion conductivity and the electronic conductivity of the one-dimensional fast ion conductor meet the above protection range, it is beneficial to transmit lithium ions and electrons, thereby facilitating the improvement of the performance of the negative electrode sheet and the battery.
[0018] Preferably, the diameter of the one-dimensional fast ion conductor is 20-100 nm, for example, it can be 20 nm, 30 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or 100 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the length of the one-dimensional fast ion conductor is 3-10 μm, for example, it can be 3 μm, 4 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the one-dimensional fast ion conductor comprises inorganic nanowires.
[0021] Preferably, the inorganic nanowires include non-metallic nanowires and / or metal-containing nanowires; the metal-containing nanowires include metal element nanowires and / or metal oxide nanowires.
[0022] Preferably, the non-metallic nanowires include silicon nanowires.
[0023] Preferably, the metal nanowires include any one of gold nanowires, silver nanowires, aluminum nanowires, magnesium nanowires, germanium nanowires, tin nanowires, titanium nanowires or gallium nanowires, or a combination of at least two thereof, preferably silver nanowires.
[0024] Preferably, the metal oxide nanowires include zinc oxide nanowires.
[0025] Preferably, based on the mass of the active material as 100%, the mass fraction of the one-dimensional fast ion conductor is 0.1%-10%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.625%, 0.7%, 0.75%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In the present invention, when the mass fraction of the one-dimensional fast ion conductor meets the above protection range, the one-dimensional fast ion conductor is evenly dispersed and agglomeration can be avoided as much as possible.
[0027] In a second aspect, the present invention provides a method for preparing the negative electrode material according to the first aspect, the preparation method comprising:
[0028] The active material and the solution containing the one-dimensional fast ion conductor are degassed and mixed, and then dried to obtain the negative electrode material, wherein the aspect ratio of the one-dimensional fast ion conductor is 50-200.
[0029] The present invention can make the one-dimensional fast ion conductor entangled and distributed on the surface of the active material through the steps of degassing, mixing and drying. The process is simple and can effectively reduce the manufacturing cost.
[0030] Preferably, the solvent in the solution containing the one-dimensional fast ion conductor includes water and / or alcohol.
[0031] In the present invention, the alcohol includes but is not limited to ethanol or isopropanol.
[0032] Preferably, in the solution containing the one-dimensional fast ion conductor, the concentration of the one-dimensional fast ion conductor is 0.001-10 mg / mL, for example, it can be 0.001 mg / mL, 0.002 mg / mL, 0.005 mg / mL, 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL or 10 mg / mL, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the mass volume ratio of the active substance and the solution containing the one-dimensional fast ion conductor is (0.01-5) g:1 mL, for example, it can be 0.01 g:1 mL, 0.05 g:1 mL, 0.1 g:1 mL, 0.5 g:1 mL, 1 g:1 mL, 1.5 g:1 mL, 2 g:1 mL, 2.5 g:1 mL, 3 g:1 mL, 3.5 g:1 mL, 4 g:1 mL, 4.5 g:1 mL or 5 g:1 mL, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0034] Preferably, the deaeration and mixing is performed in at least 2 times, for example, 2 times, 3 times, 4 times, 5 times or 8 times, preferably 2-6 times, wherein the revolution speed of each deaeration and mixing is independently 50-1000r / min, for example, 50r / min, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, and the rotation speed is independently 50-1 000r / min, for example, it can be 50r / min, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, etc., and the time is independently 100-600s, for example, it can be 100s, 200s, 300s, 400s, 500s or 600s, etc., but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0035] It should be noted that the “independently” in the phrase “the revolution speed of each deaeration and mixing is independently 50-1000 r / min” means that the revolution speed of each deaeration and mixing is selected without interfering with each other. The same applies to the rest.
[0036] The present invention defines the conditions for degassing and mixing. Under the above conditions, the one-dimensional fast ion conductor can be entangled and distributed on the surface of the active material, while preventing the one-dimensional fast ion conductor from being broken and maintaining the structural integrity of the one-dimensional fast ion conductor.
[0037] Preferably, during the degassing and mixing process, after each degassing and mixing is completed, the temperature of the system is lowered to room temperature before the next degassing and mixing is performed.
[0038] In a third aspect, the present invention provides a negative electrode plate, comprising a current collector and an active layer disposed on at least one side of the current collector; the active layer comprises the negative electrode material described in the first aspect; and the active layer also comprises a binder.
[0039] The present invention does not limit the type of the adhesive, including but not limited to polyisobutylene, styrene-butadiene rubber or nitrile rubber.
[0040] Preferably, the active layer further includes a solid electrolyte and / or a conductive agent.
[0041] In the present invention, when the active layer contains a solid electrolyte, the one-dimensional fast ion conductors in the negative electrode material are entangled with each other, which can effectively improve the cohesion of the negative electrode plate, thereby preventing the active material and the solid electrolyte from being peeled off due to volume changes or thermal stress, thereby improving the cycle performance of the battery.
[0042] Preferably, the solid electrolyte includes any one of a sulfide electrolyte, an oxide electrolyte or a polymer electrolyte, or a combination of at least two of them.
[0043] The present invention does not limit the type of sulfide electrolyte, including but not limited to Li 6 PS 5 Cl 1 , Li 5.5 PS 4.5 Cl 1.5 , Li 3 PS 4 , Li 10 G 2 S 12 、70Li 2 S·30P 2 S 5 、80Li 2 S·20P 2 S 5 or 75Li 2S·25P 2 S 5 wait.
[0044] The present invention does not limit the type of oxide electrolyte, including but not limited to perovskite-type oxide electrolyte, garnet-type oxide electrolyte, NASICON-type oxide electrolyte or LISICON-type oxide electrolyte.
[0045] The present invention does not limit the type of polymer electrolyte, including but not limited to polyethylene oxide-based electrolytes, polysiloxane-based electrolytes or aliphatic polycarbonate-based electrolytes.
[0046] The present invention does not limit the type of conductive agent, including but not limited to conductive carbon black, carbon nanotubes or graphene.
[0047] Preferably, the particle size of the solid electrolyte is 0.1-10 μm, for example, it can be 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In a fourth aspect, the present invention provides a method for preparing the negative electrode sheet according to the third aspect, the preparation method comprising:
[0049] (1) The negative electrode material, the adhesive solution containing the binder and the solvent are degassed and mixed to obtain a negative electrode slurry.
[0050] (2) The negative electrode slurry is coated on at least one side of the current collector, and then dried to obtain the negative electrode sheet.
[0051] Preferably, the deaeration and mixing raw materials in step (1) further include a solid electrolyte and / or a conductive agent.
[0052] Preferably, the negative electrode slurry comprises, by weight: 40-90 parts of negative electrode material, 0-40 parts of solid electrolyte, 0-5 parts of conductive agent, 10-70 parts of glue containing binder and 25-40 parts of solvent.
[0053] Among them, the selection range of the negative electrode material (40-90 parts) can be, for example, 40 parts, 45 parts, 50 parts, 50.5 parts, 51 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts or 85 parts, etc.; the selection range of the solid electrolyte (0-40 parts) can be, for example, 0 parts, 1 parts, 3 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts or 40 parts, etc.; the selection range of the conductive agent (0-5 parts) can be, for example, The range of the amount of the adhesive containing the binder (10-70 parts) can be, for example, 10 parts, 20 parts, 30 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts or 70 parts; the range of the amount of the solvent (25-40 parts) can be, for example, 25 parts, 30 parts, 35 parts or 40 parts, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0054] Preferably, taking the total mass of the adhesive containing the binder as 100%, the mass fraction of the binder is 1%-20%, for example, it can be 1%, 2%, 3%, 5%, 8%, 10%, 12%, 15%, 18% or 20%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] Preferably, the solvent is a first anhydrous solvent.
[0056] In the present invention, the first anhydrous solvent includes but is not limited to anhydrous p-xylene or anhydrous isobutyl isobutyrate.
[0057] Preferably, the solvent in the adhesive solution containing the binder is a second anhydrous solvent.
[0058] In the present invention, the second anhydrous solvent includes but is not limited to anhydrous p-xylene or anhydrous isobutyl isobutyrate.
[0059] The present invention adopts the first anhydrous solvent and the second anhydrous solvent in order to cooperate with the solid electrolyte (such as sulfide electrolyte) that is sensitive to water and avoid the influence of moisture on the solid electrolyte.
[0060] Preferably, the first anhydrous solvent and the second anhydrous solvent are of the same type.
[0061] Preferably, the degassing and mixing method in step (1) is one-step degassing and mixing or step-by-step degassing and mixing.
[0062] In step (1) of the present invention, when the solid raw material to be deaerated and mixed only contains negative electrode material, one-step deaeration and mixing is performed. When the solid raw material to be deaerated and mixed contains solid electrolyte and / or conductive agent in addition to negative electrode material, step-by-step deaeration and mixing is performed.
[0063] Preferably, the one-step deaeration and mixing is carried out in at least 2 times, for example, 2 times, 3 times, 4 times, 5 times or 8 times, etc., preferably 2-6 times; wherein the specific parameters of each deaeration and mixing include: orbital speed of 100-1000r / min, rotation speed of 100-1000r / min, and running time of 300-600s. Among them, the revolution speed can be, for example, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 550r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, etc., the rotation speed can be, for example, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 550r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, etc., the running time can be, for example, 300s, 400s, 500s or 600s, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] The present invention defines the conditions for one-step degassing and mixing. Under the above conditions, the components can be mixed evenly, while the one-dimensional fast ion conductor can be prevented from being broken and the structural integrity of the one-dimensional fast ion conductor can be maintained.
[0065] Preferably, the stepwise degassing and mixing comprises: firstly performing a first degassing and mixing of the negative electrode material and at least one of the solid electrolyte and the conductive agent, and then performing a second degassing and mixing of the first degassing and mixing product with a glue solution containing a binder and a solvent.
[0066] In the present invention, when multiple solid raw materials are contained, the multiple solid raw materials are first subjected to dry degassing and mixing, and then the obtained mixed material is subjected to wet degassing and mixing with a glue solution containing a binder and a solvent, so that the components can be mixed more evenly; wherein the multiple solid raw materials include, in addition to the negative electrode material, a solid electrolyte and / or a conductive agent.
[0067] Preferably, the first deaeration and mixing is carried out at least 2 times, for example, 2 times, 3 times, 4 times, 5 times or 8 times, etc., preferably 2-6 times; wherein each deaeration and mixing is carried out according to step A; the step A specifically includes: firstly carrying out a deaeration and mixing at an orbital speed of 100-1000r / min, an autorotation speed of 100-1000r / min and a running time of 100-600s, and then carrying out a second deaeration and mixing at an orbital speed of 100-1000r / min, an autorotation speed of 100-1000r / min and a running time of 100-600s.
[0068] In the primary deaeration and mixing of step A, the revolution speed may be, for example, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 550 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min or 1000 r / min, etc., the rotation speed may be, for example, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 550 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min or 1000 r / min, etc., and the operation time may be, for example, 100 s, 200 s, 300 s, 400 s, 500 s or 600 s, etc.; in the secondary deaeration and mixing of step A, the revolution speed may be, for example, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 550 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min or 1000 r / min, etc. The rotation speed may be, for example, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 550r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, etc. The rotation speed may be, for example, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 550r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, etc. The running time may be, for example, 100s, 200s, 300s, 400s, 500s or 600s, etc., but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0069] Preferably, the second deaeration and mixing is carried out in at least 2 times, for example, 2 times, 3 times, 4 times, 5 times or 8 times, etc., preferably 2-6 times; wherein each deaeration and mixing is carried out according to step B; the step B specifically comprises: firstly carrying out primary deaeration and mixing at an orbital speed of 100-1000r / min, an autorotation speed of 100-1000r / min and a running time of 50-300s, and then carrying out secondary deaeration and mixing at an orbital speed of 100-1000r / min, an autorotation speed of 100-1000r / min and a running time of 100-500s.
[0070] In the primary deaeration and mixing of step B, the revolution speed may be, for example, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 550r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, the rotation speed may be, for example, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 550r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, and the operation time may be, for example, 50s, 100s, 150s, 200s, 250s or 300s, etc.; in the secondary deaeration and mixing of step B, the The revolution speed may be, for example, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 550r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, etc., the rotation speed may be, for example, 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 550r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, etc., the running time may be, for example, 100s, 200s, 300s, 400s or 500s, etc., but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0071] The present invention defines the conditions for step-by-step degassing and mixing. Under the above conditions, the components can be mixed evenly, while the one-dimensional fast ion conductor can be prevented from being broken and the structural integrity of the one-dimensional fast ion conductor can be maintained.
[0072] It should be noted that in the one-step degassing and mixing or step-by-step degassing and mixing process of the present invention, after each degassing and mixing is completed, the system temperature is lowered to room temperature (25±5°C) before the next degassing and mixing is performed. In addition, in the one-step degassing and mixing or step-by-step degassing and mixing process, the parameters of each degassing and mixing can be selected independently without interfering with each other.
[0073] In a fifth aspect, the present invention provides a secondary battery, wherein the negative electrode plate of the secondary battery includes the negative electrode material described in the first aspect, or the secondary battery includes the negative electrode plate described in the third aspect.
[0074] Preferably, the secondary battery includes an all-solid-state battery, a quasi-solid-state battery, a semi-solid-state battery or a liquid battery.
[0075] Generally, all-solid-state batteries, quasi-solid-state batteries, semi-solid-state batteries and liquid batteries are distinguished according to the proportion of liquid electrolyte in the battery cell. Specifically: all-solid-state batteries are 0wt%, quasi-solid-state batteries are 0-5wt% and not 0wt%, semi-solid-state batteries are 5-10wt% and not 5wt%, and liquid batteries are greater than 10wt%.
[0076] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0077] Compared with the prior art, the present invention has the following beneficial effects:
[0078] (1) In the negative electrode material provided by the present invention, a one-dimensional fast ion conductor is entangled and distributed on the surface of the active material. Due to the limitation of the one-dimensional structure of the fast ion conductor, lithium ions can only be transmitted along a one-dimensional direction. Therefore, when the negative electrode material is used to prepare the negative electrode plate, the tortuosity of lithium ion transmission can be effectively reduced, so that the lithium ions on the surface of the negative electrode plate can be quickly transmitted to the interior of the entire negative electrode along the one-dimensional fast ion conductor, thereby effectively preventing the lithium ions from aggregating and precipitating on the surface of the negative electrode, thereby increasing the charging rate of the battery, improving the rate performance, and reducing the risk of battery short circuit.
[0079] (2) The one-dimensional fast ion conductor of the present invention has a high aspect ratio. The one-dimensional fast ion conductors are entangled with each other, which can effectively improve the cohesion of the pole piece, thereby avoiding the influence of volume change or thermal stress on the pole piece, which helps to improve the cycle performance of the battery. At the same time, the one-dimensional fast ion conductor with a limited aspect ratio range can be used to allow the one-dimensional fast ion conductor to be evenly wound on the surface of the active material to avoid agglomeration, thereby reducing the tortuosity of lithium ion transmission and enabling the battery to achieve fast charging and discharging.
[0080] (3) The one-dimensional fast ion conductor of the present invention has a stable structure and can repeatedly insert and remove lithium without being pulverized or broken. In addition, the one-dimensional fast ion conductor is relatively soft and will not break brittlely during the battery assembly process, thus maintaining a complete structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] Figure 1 This is a SEM image of the negative electrode material provided in Example 1 of the present invention.
[0082] Figure 2 This is another SEM image of the negative electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0083] The technical scheme of the present invention is further described below by specific implementation methods. For ease of understanding the present invention, the present invention lists the following embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0084] It should be noted that the room temperature in the following specific embodiments refers to 25±5°C.
[0085] Example 1
[0086] This embodiment provides a negative electrode material, which includes an active material and a one-dimensional fast ion conductor entangled and distributed on the surface of the active material; the active material is a graphite primary particle with a particle size of 10-15 μm; the one-dimensional fast ion conductor is a silver nanowire, the silver nanowire has a diameter of 50 nm, a length of 5 μm, an aspect ratio of 100, and a lithium ion conductivity of about 10 -3 S / cm, and the electronic conductivity is 6.3×10 7 S / cm; taking the mass of active material as 100%, the mass fraction of silver nanowires is 1.43%.
[0087] This embodiment also provides a method for preparing the above-mentioned negative electrode material, and the preparation method comprises the following steps:
[0088] 3 g of primary graphite particles were placed in a mixing tank, and then 4.35 mL of a silver nanowire solution was added, wherein the concentration of the silver nanowire solution was 10 mg / mL, and the solvent was isopropanol; the mixing tank was then placed in a double-station planetary deaerator for deaeration and mixing, and the deaeration and mixing were performed in 5 steps, wherein the revolution speed of each deaeration and mixing was 690 r / min, the rotation speed was 414 r / min, and the time was 300 s. After each deaeration and mixing was completed, the system temperature was lowered to room temperature before the next deaeration and mixing was performed; and then the mixture was dried at 80° C. for 48 h to obtain the negative electrode material.
[0089] Figure 1 and Figure 2 The morphology of the negative electrode material provided in this embodiment is shown. From the figure, it can be seen that the one-dimensional fast ion conductor (silver nanowire) is successfully wound and distributed on the graphite surface.
[0090] Example 2
[0091] This embodiment provides a negative electrode material, which includes an active material and a one-dimensional fast ion conductor entangled and distributed on the surface of the active material; the active material is a graphite primary particle with a particle size of 10-15 μm; the one-dimensional fast ion conductor is a silver nanowire, the silver nanowire has a diameter of 50 nm, a length of 5 μm, an aspect ratio of 100, and a lithium ion conductivity of about 10 -3S / cm, and the electronic conductivity is 6.3×10 7 S / cm; taking the mass of active material as 100%, the mass fraction of silver nanowires is 3%.
[0092] This embodiment also provides a method for preparing the above-mentioned negative electrode material, and the preparation method comprises the following steps:
[0093] 3 g of primary graphite particles were placed in a mixing tank, and then 9.28 mL of silver nanowire solution was added, wherein the concentration of the silver nanowire solution was 10 mg / mL, and the solvent was isopropanol; the mixing tank was then placed in a double-station planetary deaerator for deaeration and mixing, and the deaeration and mixing were performed 6 times, wherein the revolution speed of each deaeration and mixing was 690 r / min, the rotation speed was 414 r / min, and the time was 300 s. After each deaeration and mixing was completed, the system temperature was lowered to room temperature before the next deaeration and mixing was performed; and then the mixture was dried at 80° C. for 48 h to obtain the negative electrode material.
[0094] Example 3
[0095] This embodiment provides a negative electrode material, which includes an active material and a one-dimensional fast ion conductor entangled and distributed on the surface of the active material; the active material is a graphite primary particle with a particle size of 10-15 μm; the one-dimensional fast ion conductor is a silver nanowire, the silver nanowire has a diameter of 50 nm, a length of 5 μm, an aspect ratio of 100, and a lithium ion conductivity of about 10 -3 S / cm, and the electronic conductivity is 6.3×10 7 S / cm; taking the mass of active material as 100%, the mass fraction of silver nanowires is 6%.
[0096] This embodiment also provides a method for preparing the above-mentioned negative electrode material, and the preparation method comprises the following steps:
[0097] 1.5 g of primary graphite particles were placed in a mixing tank, and then 9.57 mL of silver nanowire solution was added, wherein the concentration of the silver nanowire solution was 10 mg / mL, and the solvent was isopropanol; the mixing tank was then placed in a double-station planetary deaerator for deaeration and mixing, and the deaeration and mixing were performed in 6 steps, wherein the revolution speed of each deaeration and mixing was 690 r / min, the rotation speed was 414 r / min, and the time was 300 s. After each deaeration and mixing was completed, the system temperature was lowered to room temperature before the next deaeration and mixing was performed; and then the mixture was dried at 80° C. for 48 h to obtain the negative electrode material.
[0098] Example 4
[0099] The difference between this embodiment and embodiment 1 is that the silver nanowires are replaced with titanium nanowires, whose lithium ion conductivity is about 10-4 S / cm, and the electronic conductivity is 1.724×10 5 S / cm.
[0100] The remaining parameters remain the same as those in Example 1.
[0101] Example 5
[0102] The difference between this embodiment and embodiment 1 is that, based on the mass of the active material being 100%, the mass fraction of the silver nanowires is 0.5%.
[0103] The remaining parameters remain the same as those in Example 1.
[0104] Example 6
[0105] The difference between this embodiment and embodiment 1 is that, based on the mass of the active material being 100%, the mass fraction of the silver nanowires is 10.5%.
[0106] The remaining parameters remain the same as those in Example 1.
[0107] Example 7
[0108] The difference between this embodiment and embodiment 1 is that in the process of preparing the negative electrode material, the degassing and mixing process is only performed once, and the process parameters are: maintaining an orbital speed of 690 r / min, a rotational speed of 414 r / min, and mixing for a total of 1400 s.
[0109] The remaining parameters remain the same as those in Example 1.
[0110] Comparative Example 1
[0111] The difference between this comparative example and Example 1 is that the one-dimensional fast ion conductor is omitted.
[0112] The remaining parameters remain the same as those in Example 1.
[0113] Comparative Example 2
[0114] The difference between this comparative example and Example 1 is that the diameter of the silver nanowire is 50 nm, the length is 1.5 μm, and the aspect ratio is 30.
[0115] The remaining parameters remain the same as those in Example 1.
[0116] Comparative Example 3
[0117] The difference between this comparative example and Example 1 is that the diameter of the silver nanowire is 50 nm, the length is 14 μm, and the aspect ratio is 280.
[0118] The remaining parameters remain the same as those in Example 1.
[0119] Application Example 1
[0120] This application example provides a negative electrode plate, which includes a copper foil and an active layer disposed on both sides of the copper foil; the active layer includes the negative electrode material provided in Example 1, a solid electrolyte and a binder; the solid electrolyte is a sulfide electrolyte (Li 5.5 PS 4.5 Cl 1.5 ), the particle size is 1-2 μm; the binder is polyisobutylene; the mass ratio of the negative electrode material, the solid electrolyte and the binder is 71:24:5.
[0121] This application example provides a method for preparing the above-mentioned negative electrode sheet, and the preparation method comprises the following steps:
[0122] (1) By weight, 71 parts of the negative electrode material provided in Example 1 were placed in a mixing tank, and then 24 parts of sulfide electrolyte were added. The mixing tank was sealed with a sealing film and then placed in a double-station planetary degassing mixer for degassing and mixing. The degassing and mixing were carried out in 4 times, wherein each degassing and mixing was first carried out at an orbital speed of 690 r / min, an autogenous rotation speed of 414 r / min and a running time of 300 s, and then a second degassing and mixing was carried out at an orbital speed of 940 r / min, an autogenous rotation speed of 940 r / min and a running time of 300 s; after each degassing and mixing was completed, the system temperature was cooled to room temperature before the next degassing and mixing was carried out; after the mixing was completed, the mixing tank was transferred to a glove box to obtain a mixing tank containing the mixed material.
[0123] (2) Add 62.5 parts of polyisobutylene glue and 39 parts of anhydrous p-xylene to a mixing tank containing the mixed material, wherein the mass fraction of polyisobutylene is 8% based on the total mass of the polyisobutylene glue as 100%; the solvent in the polyisobutylene glue is anhydrous p-xylene; then seal the mixing tank with a sealing film, and then put it into a double-station planetary degassing mixer for degassing and mixing, wherein each degassing and mixing is first performed at a revolution speed of 690 r / min, a rotation speed of 414 r / min and a running time of 300 s for a first-level degassing and mixing, and then at a revolution speed of 940 r / min, a rotation speed of 940 r / min and a running time of 300 s for a second-level degassing and mixing; after each degassing and mixing is completed, wait for the system temperature to drop to room temperature before performing the next degassing and mixing; after the mixing is completed, transfer the mixing tank to a glove box to obtain a negative electrode slurry.
[0124] (3) The negative electrode slurry is coated on both sides of the copper foil, and then dried to obtain the negative electrode sheet.
[0125] Application Example 2
[0126] This application example provides a negative electrode plate, which includes a copper foil and an active layer disposed on both sides of the copper foil; the active layer includes the negative electrode material provided in Example 2, a solid electrolyte and a binder; the solid electrolyte is a sulfide electrolyte (Li 5.5 PS 4.5 Cl 1.5 ), the particle size is 1-2 μm; the binder is polyisobutylene; the mass ratio of the negative electrode material, the solid electrolyte and the binder is 73.5:22.5:4.
[0127] This application example provides a method for preparing the above-mentioned negative electrode sheet, and the preparation method comprises the following steps:
[0128] (1) By weight, 73.5 parts of the negative electrode material provided in Example 2 were placed in a mixing tank, and then 22.5 parts of sulfide electrolyte were added. The mixing tank was sealed with a sealing film and then placed in a double-station planetary degassing mixer for degassing and mixing. The degassing and mixing were carried out in 4 times, wherein each degassing and mixing was first carried out at an orbital speed of 690 r / min, an autogenous rotation speed of 414 r / min and a running time of 300 s, and then a second degassing and mixing was carried out at an orbital speed of 940 r / min, an autogenous rotation speed of 940 r / min and a running time of 300 s; after each degassing and mixing was completed, the system temperature was cooled to room temperature before the next degassing and mixing was carried out; after the mixing was completed, the mixing tank was transferred to a glove box to obtain a mixing tank containing the mixed material.
[0129] (2) Add 50 parts of polyisobutylene glue and 39 parts of anhydrous p-xylene to a mixing tank containing the mixed material, wherein the mass fraction of polyisobutylene is 8% based on the total mass of the polyisobutylene glue as 100%; the solvent in the polyisobutylene glue is anhydrous p-xylene; then seal the mixing tank with a sealing film, and then put it into a double-station planetary degassing mixer for degassing and mixing, wherein each degassing and mixing is first performed at a revolution speed of 690 r / min, a rotation speed of 414 r / min and a running time of 300 s for a first-level degassing and mixing, and then at a revolution speed of 940 r / min, a rotation speed of 940 r / min and a running time of 300 s for a second-level degassing and mixing; after each degassing and mixing is completed, wait for the system temperature to drop to room temperature before performing the next degassing and mixing; after the mixing is completed, transfer the mixing tank to a glove box to obtain a negative electrode slurry.
[0130] (3) The negative electrode slurry is coated on both sides of the copper foil, and then dried to obtain the negative electrode sheet.
[0131] Application Example 3-7
[0132] The difference from Application Example 1 is that the negative electrode material provided in Example 1 is replaced by the negative electrode materials provided in Example 3, Example 4, Example 5, Example 6 and Example 7 respectively.
[0133] The remaining parameters are the same as those in Application Example 1.
[0134] Application Example 8
[0135] This application example provides a negative electrode plate, which includes a copper foil and an active layer arranged on both sides of the copper foil; the active layer includes the negative electrode material and the binder provided in Example 1; the binder is polyisobutylene; the mass ratio of the negative electrode material to the binder is 97:3.
[0136] This application example provides a method for preparing the above-mentioned negative electrode sheet, and the preparation method comprises the following steps:
[0137] (1) By weight, 97 parts of the negative electrode material provided in Example 1 were placed in a mixing tank, and then 37.5 parts of polyisobutylene glue and 48.7 parts of anhydrous p-xylene were added to the mixing tank, wherein the mass fraction of polyisobutylene was 8% based on the total mass of the polyisobutylene glue as 100%; the solvent in the polyisobutylene glue was anhydrous p-xylene; the mixing tank was then sealed with a sealing film, and then placed in a double-station planetary degassing mixer for degassing and mixing, the degassing and mixing was carried out in 4 times, wherein each degassing and mixing was carried out at a revolution speed of 690 r / min and a rotation speed of 414 r / min for 300 s; after each degassing and mixing was completed, the system temperature was cooled to room temperature before the next degassing and mixing was carried out; after the mixing was completed, the mixing tank was transferred to a glove box to obtain a negative electrode slurry.
[0138] (2) The negative electrode slurry is coated on both sides of the copper foil, and then dried to obtain the negative electrode sheet.
[0139] Application Example 9
[0140] This application example provides a negative electrode plate, which includes a copper foil and an active layer disposed on both sides of the copper foil; the active layer includes the negative electrode material provided in Example 2, a solid electrolyte, a conductive agent and a binder; the solid electrolyte is a sulfide electrolyte (Li 5.5 PS 4.5 Cl 1.5 ), the particle size is 1-2μm; the conductive agent is C45; the binder is polyisobutylene; the mass ratio of the negative electrode material, the solid electrolyte, the conductive agent and the binder is 73.5:21.5:1:4.
[0141] This application example provides a method for preparing the above-mentioned negative electrode sheet, and the preparation method comprises the following steps:
[0142] (1) By weight, 73.5 parts of the negative electrode material provided in Example 4 were placed in a mixing tank, and then 21.5 parts of a solid electrolyte and 1 part of a conductive agent were added. The mixing tank was sealed with a sealing film and then placed in a double-station planetary degassing mixer for degassing and mixing. The degassing and mixing were carried out in 4 times, wherein each degassing and mixing was first carried out at an orbital speed of 690 r / min, an autogenous rotation speed of 414 r / min and a running time of 300 s, and then a second degassing and mixing was carried out at an orbital speed of 940 r / min, an autogenous rotation speed of 940 r / min and a running time of 300 s; after each degassing and mixing was completed, the system temperature was cooled to room temperature before the next degassing and mixing was carried out; after the mixing was completed, the mixing tank was transferred to a glove box to obtain a mixing tank containing the mixed material.
[0143] (2) Add 50 parts of polyisobutylene glue and 40 parts of anhydrous p-xylene to a mixing tank containing the mixed material, wherein the mass fraction of polyisobutylene is 8% based on the total mass of the polyisobutylene glue as 100%; the solvent in the polyisobutylene glue is anhydrous p-xylene; then seal the mixing tank with a sealing film, and then put it into a double-station planetary degassing mixer for degassing and mixing, wherein each degassing and mixing is first performed at a revolution speed of 690 r / min, a rotation speed of 414 r / min and a running time of 300 s for a first-level degassing and mixing, and then at a revolution speed of 940 r / min, a rotation speed of 940 r / min and a running time of 300 s for a second-level degassing and mixing; after each degassing and mixing is completed, wait for the system temperature to drop to room temperature before performing the next degassing and mixing; after the mixing is completed, transfer the mixing tank to a glove box to obtain a negative electrode slurry.
[0144] (3) The negative electrode slurry is coated on both sides of the copper foil, and then dried to obtain the negative electrode sheet.
[0145] Comparative Application Examples 1-3
[0146] The difference from Application Example 1 is that the negative electrode material provided in Example 1 is replaced by the negative electrode materials provided in Comparative Example 1, Comparative Example 2 and Comparative Example 3 respectively.
[0147] The remaining parameters are the same as those in Application Example 1.
[0148] Performance Testing
[0149] The negative electrode sheets provided in the above application examples and comparative application examples are cut and respectively 5.5 PS 4.5 Cl 1.5 Sulfide solid electrolyte and LiNi 0.8 Co 0.1 Mn 0.1 O 2(NCM811) The positive electrode plates are assembled into an all-solid-state battery, in which the areas of the negative electrode plates are equal to those of the positive electrode plates.
[0150] The following tests are performed on all-solid-state batteries:
[0151] (1) Rate performance and first effect test:
[0152] At 55℃ and 100MPa, the battery was charged / discharged at 0.05C, 0.1C, 0.2C, 0.33C, 0.5C, 1.0C, 1.5C and 2.0C in sequence using a blue power test system. Each rate was charged / discharged for 5 cycles. If a short circuit occurred during the test, the test was stopped and the first cycle discharge capacity of the battery at each charge / discharge rate was recorded. The first efficiency of the battery was also recorded, and the first efficiency = the first cycle discharge capacity at 0.05C / the first cycle charge capacity at 0.05C.
[0153] (2) Calculation of limiting current density:
[0154] The maximum current of the battery is tested by the blue electric test system, and then the limiting current density is calculated. The limiting current density = maximum current / positive electrode area.
[0155] The test results are shown in Table 1.
[0156] Table 1
[0157]
[0158] analyze:
[0159] It can be seen from Application Examples 1-3 that in the negative electrode material of the present invention, silver nanowires are entangled and distributed on the surface of the active material. Due to the limitations of the one-dimensional structure of the silver nanowires, as well as the high electronic conductivity of the silver nanowires themselves and the high lithium ion conductivity after lithium insertion, the negative electrode material provided by the present invention is used to prepare the negative electrode plate, which can reduce the tortuosity of lithium ion transmission and the tortuosity of electron transmission, and the negative electrode plate has a high lithium ion transmission rate and electron transmission rate. The assembled all-solid-state battery exhibits high first efficiency and discharge specific capacity, excellent rate performance and high limiting current density.
[0160] It can be seen from Application Examples 1 and 4 that when silver nanowires are replaced by titanium nanowires, the lithium ion conductivity and electron conductivity of the nanowires decrease, which will affect the lithium ion transfer rate and electron transfer rate of the negative electrode sheet, and further affect the rate performance of the battery.
[0161] It can be seen from Application Examples 1 and 5-6 that when the mass fraction of the one-dimensional fast ion conductor is within the protection range, it is conducive to the uniform dispersion of the one-dimensional fast ion conductor; when the mass fraction of the one-dimensional fast ion conductor is too small, the number of one-dimensional fast ion conductors is too small, and the improvement effect is not obvious; when the mass fraction of the one-dimensional fast ion conductor is too large, it will cause the one-dimensional fast ion conductor to agglomerate, affecting lithium ion transmission and battery performance.
[0162] It can be seen from Application Examples 1 and 7 that in the process of preparing negative electrode materials, if the degassing and mixing are not carried out in batches, the slurry will be unevenly dispersed, resulting in uneven electrode sheets, affecting the transmission of lithium ions and even causing a short circuit.
[0163] It can be seen from Application Examples 1 and 8 that, compared with Application Example 1, no solid electrolyte is added to the negative electrode plate of Application Example 8, and 2C charging / discharging without short circuit can be achieved, proving that silver nanowires have good electron and lithium ion conductivity, but the capacity decays rapidly at high rates, indicating that more silver nanowires need to be added at high rates or the assistance of solid electrolytes is needed.
[0164] It can be seen from Application Examples 2 and 9 that the performance of the two groups of negative electrode sheets is not much different. The negative electrode sheet of Application Example 2 can still perform well without adding the conductive agent C45, which shows that the addition of silver nanowires significantly improves the electronic conductivity of the sheet. In addition, from a process point of view, eliminating C45 is more conducive to the dispersion of the slurry.
[0165] It can be seen from Application Example 1 and Comparative Application Example 1 that Comparative Application Example 1 uses traditional graphite materials to prepare negative electrode plates. When the assembled all-solid-state battery is running, lithium ions randomly jump between solid electrolyte particles, and the lithium ion transmission tortuosity of the plate is high, resulting in poor battery performance. If the amount of solid electrolyte is increased, the transmission tortuosity can be reduced, but at the same time, the energy density of the all-solid-state battery will be reduced, which is not expected. Compared with Comparative Application Example 1, the battery rate performance of Application Example 1 of the present invention is significantly improved, the first efficiency is increased by more than 0.5%, the first cycle discharge capacity is significantly improved, and the discharge capacity is improved while improving the high rate current charge and discharge capacity, from 0.5C charge / discharge without short circuit to 2C charge / discharge without short circuit, and the limiting current density is increased to more than three times the original. Therefore, the one-dimensional fast ion conductor modified negative electrode provided by the present invention can effectively improve the first efficiency, discharge capacity, rate performance and limiting current density of the battery.
[0166] It can be seen from Application Example 1 and Comparative Application Examples 2-3 that when the aspect ratio of silver nanowires is within the protection range, graphite can be better modified, the tortuosity of lithium ion transmission can be reduced, and the all-solid-state battery exhibits high first efficiency and discharge specific capacity, excellent rate performance and high limiting current density. When the aspect ratio of silver nanowires is too small, the transmission path of lithium ions in fast ion conductors is short, and the lithium ion transmission rate is not significantly improved; when the aspect ratio of silver nanowires is too large, the silver nanowires themselves will be entangled and agglomerated, the silver nanowires will be unevenly dispersed inside the pole piece, and the lithium ion transmission speed will be uneven, affecting battery performance.
[0167] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A negative electrode material, characterized in that: The negative electrode material includes an active substance and a one-dimensional fast ion conductor entangled and distributed on the surface of the active substance; The aspect ratio of the one-dimensional fast ion conductor is 50-200.
2. The negative electrode material according to claim 1, characterized in that The active material includes graphite and / or silicon-carbon material; Preferably, the particle size of the active substance is in the range of 1-50 μm.
3. The negative electrode material according to claim 1 or 2, characterized in that: The lithium ion conductivity of the one-dimensional fast ion conductor is ≥10 -5 S / cm; Preferably, the electronic conductivity of the one-dimensional fast ion conductor is greater than 10 -6 S / cm; Preferably, the diameter of the one-dimensional fast ion conductor is 20-100 nm; Preferably, the length of the one-dimensional fast ion conductor is 3-10 μm; Preferably, the one-dimensional fast ion conductor comprises an inorganic nanowire; Preferably, the inorganic nanowires include non-metallic nanowires and / or metal-containing nanowires; the metal-containing nanowires include metal element nanowires and / or metal oxide nanowires; Preferably, the non-metallic nanowires include silicon nanowires; Preferably, the metal nanowires include any one of gold nanowires, silver nanowires, aluminum nanowires, magnesium nanowires, germanium nanowires, tin nanowires, titanium nanowires or gallium nanowires, or a combination of at least two thereof, preferably silver nanowires; Preferably, the metal oxide nanowires include zinc oxide nanowires; Preferably, based on 100% of the mass of the active material, the mass fraction of the one-dimensional fast ion conductor is 0.1%-10%.
4. A method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The active material and the solution containing the one-dimensional fast ion conductor are degassed and mixed, and then dried to obtain the negative electrode material, wherein the aspect ratio of the one-dimensional fast ion conductor is 50-200.
5. The preparation method according to claim 4, characterized in that: In the solution containing the one-dimensional fast ion conductor, the concentration of the one-dimensional fast ion conductor is 0.001-10 mg / mL; Preferably, the mass volume ratio of the active material and the solution containing the one-dimensional fast ion conductor is (0.01-5) g:1 mL; Preferably, the deaeration and mixing is performed in at least 2 times, wherein the revolution speed of each deaeration and mixing is independently 50-1000 r / min, the rotation speed is independently 50-1000 r / min, and the time is independently 100-600 s.
6. A negative electrode plate, characterized in that: The negative electrode plate comprises a current collector and an active layer disposed on at least one side surface of the current collector; The active layer comprises the negative electrode material according to any one of claims 1 to 3; The active layer also includes a binder.
7. The negative electrode sheet according to claim 6, characterized in that: The active layer also includes a solid electrolyte and / or a conductive agent; Preferably, the particle size of the solid electrolyte is 0.1-10 μm.
8. A method for preparing a negative electrode sheet according to claim 6 or 7, characterized in that: The preparation method comprises: (1) Degassing and mixing the negative electrode material, the adhesive solution containing the binder and the solvent to obtain a negative electrode slurry; (2) The negative electrode slurry is coated on at least one side of the current collector, and then dried to obtain the negative electrode sheet.
9. The preparation method according to claim 8, characterized in that: The deaerated mixed raw materials in step (1) further include a solid electrolyte and / or a conductive agent; Preferably, the negative electrode slurry comprises, by weight: 40-90 parts of negative electrode material, 0-40 parts of solid electrolyte, 0-5 parts of conductive agent, 10-70 parts of glue containing binder and 25-40 parts of solvent; Preferably, based on the total mass of the adhesive solution containing the binder being 100%, the mass fraction of the binder is 1%-20%; Preferably, the degassing and mixing method in step (1) is one-step degassing and mixing or step-by-step degassing and mixing; Preferably, the one-step degassing and mixing is performed in at least 2 times, wherein the specific parameters of each degassing and mixing include: the revolution speed is 100-1000r / min, the rotation speed is 100-1000r / min, and the running time is 300-600s; Preferably, the stepwise degassing and mixing comprises: firstly performing a first degassing and mixing of the negative electrode material and at least one of the solid electrolyte and the conductive agent, and then performing a second degassing and mixing of the first degassing and mixing product with a binder-containing glue and a solvent; Preferably, the first degassing and mixing is performed at least twice, wherein each degassing and mixing is performed according to step A; the step A specifically comprises: firstly performing a degassing and mixing at an orbital speed of 100-1000 r / min, an autorotation speed of 100-1000 / min and a running time of 100-600 s, and then performing a second degassing and mixing at an orbital speed of 100-1000 r / min, an autorotation speed of 100-1000 r / min and a running time of 100-600 s; Preferably, the second deaeration and mixing is carried out in at least 2 times, wherein each deaeration and mixing is carried out according to step B; the step B specifically comprises: firstly carrying out primary deaeration and mixing at an orbital speed of 100-1000r / min, an autorotation speed of 100-1000r / min and a running time of 50-300s, and then carrying out secondary deaeration and mixing at an orbital speed of 100-1000r / min, an autorotation speed of 100-1000r / min and a running time of 100-500s.
10. A secondary battery, characterized in that: The negative electrode plate of the secondary battery includes the negative electrode material according to any one of claims 1 to 3, or the secondary battery includes the negative electrode plate according to claim 6 or 7.